2012
DOI: 10.1007/s00402-012-1509-4
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement in patients with history of illicit injecting drug use

Abstract: We use this unacceptable high failure rate as evidence when counseling patients and their health care professionals about the appropriate treatment of osteoarthritis in patients with a history of illicit drug use. Furthermore, we support the request of hair analysis for drugs documenting abstinence of at least 1 year before indicating THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Although individuals who misuse drugs are thought to be at increased risk of inflammatory arthropathies, the indication for surgery in this population is complicated by a higher risk of infection [7,8]. The results of this study show that patients who misuse drugs face prolonged hospital lengths of stay and higher odds of leaving against medical advice, mortality and complications following primary THA or TKA.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Although individuals who misuse drugs are thought to be at increased risk of inflammatory arthropathies, the indication for surgery in this population is complicated by a higher risk of infection [7,8]. The results of this study show that patients who misuse drugs face prolonged hospital lengths of stay and higher odds of leaving against medical advice, mortality and complications following primary THA or TKA.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to joint prosthesis infection, the present study showed that other device complications were also higher in the drug misusers group. Wieser et al [7], retrospectively analyzed 27 primary THAs in patients with a history of drug use and found the five-and 10-year implant survival rates with failure for any reason were 61% and 52.3% and for septic reasons were 70.6% and 60.5%, respectively. The risk of infection is increased by the use of drugs [9,10] and the rate of periprosthetic joint infection after bacteremia, like that often seen in drug abusers, is reported to range from 30 to 40% [30].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations